Structure of the Major G‑Quadruplex in the Human EGFR Oncogene Promoter Adopts a Unique Folding Topology with a Distinctive Snap-Back Loop - Liu, Yushuang; Li, Jinzhu; Zhang, Yongqiang; Wang, Yingying; Chen, Juannan; Bian, Yuting; Xia, Yuanzheng; Yang, Ming-Hua; Zheng, Kewei; Wang, Kai-Bo; Kong, Ling-Yi (Journal of the American Chemical Society, 2023)
EGFR tyrosine kinase inhibitors have made remarkable success in targeted cancer therapy. However, therapeutic resistance inevitably occurred and EGFR-targeting therapy has been demonstrated to have limited efficacy or utility in glioblastoma, colorectal cancer, and hepatocellular carcinoma. Therefore, there is a high demand for the development of new targets to inhibit EGFR signaling. Herein, we found that the EGFR oncogene proximal promoter sequence forms a unique type of snap-back loop containing G-quadruplex (G4), which can be targeted by small molecules. For the first time, we determined the NMR solution structure of this snap-back EGFR-G4, a three-tetrad-core, parallel-stranded G4 with naturally occurring flanking residues at both the 5′-end and 3′-end. The snap-back loop located at the 3′-end region forms a stable capping structure through two stacked G-triads connected by multiple potential hydrogen bonds. Notably, the flanking residues are consistently absent in reported snap-back G4s, raising the question of whether such structures truly exist under in vivo conditions. The resolved EGFR-G4 structure has eliminated the doubt and showed distinct structural features that distinguish it from the previously reported snap-back G4s, which lack the flanking residues. Furthermore, we found that the snap-back EGFR-G4 structure is highly stable and can form on an elongated DNA template to inhibit DNA polymerase. The unprecedented high-resolution EGFR-G4 structure has thus contributed a promising molecular target for developing alternative EGFR signaling inhibitors in cancer therapeutics. Meanwhile, the two stacked triads may provide an attractive site for specific small-molecule targeting.